Kitab Mir’at al-Ṭullāb dan Penerapan Fiqh Iṣlāḥ dalam Konflik Komunal pada Masa 'Abd al-Ra'ūf al-Sinkīlī - Zainal Muttaqin (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2020)
The Mir’at al-Ṭullāb written by al-Sinkīlī in the seventeenth century apparently did not mention the requirement of being male to become a head of state (sultan). This is interesting because the Shāfi‘ī school of fiqh which is used as a reference actually mentions this condition. Therefore, it is necessary to pay attention to the factors underlying it. Based on the literature studies and looking at the social history of the Acehnese people at that time, it can be found that the book was written when the Acehnese were polarized and there were conflicts between different religious and political groups. The conflict was very severe and was able to threaten the unity and power of the sultan at that time. The exclusion of being male as one of the requirements for public office (political authority or judge) is a manifestation of the application of Islamic jurisprudence by al-Sinkīlī which was introduced from the Qur’ān and the Sunnah so that it became legitimate (shar‘ī) while at the same time strengthening the position of the sultan, the idea of which was eventually able to reduce the political conflict in the community.